PERFORMANCES OF ACACIA SPECIES IN THAILAND - Chittachamnonk, Pravit; Sirilak, Sumet (วารสารวนศาสตร์ไทย, 2022)
Twelve Australian Acacia species were introduced in field trials in Thailand. These feild trials were established in 1985 as a collaborative research work between the Royal Forest Department (RFD) of Thailand and the Australian Centre for International Agricultural Research (ACIAR) of Australia. A total of 23 seedlots of 12 Acacia species were planted in six trial sites throughout Thailand. The result in growth performance of these Acacias at 36 month after planting showed a very significant difference between species and seedlots. The best three species were Acacia crassicarpa, Acacia auriculiformis, and Acacia aulacocarpa all from Papua New Guinea which exhibited good growth performance at almost every trial sites. On the other hand, A. aulacocarpa from Queensland, A. cincinnata, A. shirleyi, A. melanoxylon, and A. polystachya were the slowest growing Acacia species in all trial sites. Survival percentage between species also showed significant difference within site except at Sisaket which showed the best survival percentage in all species. Trial sites at Chantaburi and Prachuap Kiri Khan had the overall lowest survival percentage. However, A. auriculiformis showed the best survival percentage at all site followed by A. aulacocarpa and A. crassicarpa.